Using public participation within land use change scenarios for analysing environmental and socioeconomic drivers - Jessica Penny; Slobodan Djordjević; Albert S Chen (Environmental Research Letters, 2022)
This paper aims to improve the understanding of environmental and socioeconomic drivers on land use change (LUC) through public participation (PP), and provide recommendations for long-term policy making to support sustainable land use (LU) management. PP was necessary to help understand and address the problem and concerns of stakeholders within the study area. Through two collaboration workshops seven individual future LU scenarios were created. Using the future land use simulation model, LU was projected up till 2060, after which logistic regression analysis took place to find the most significant driver. Results found that LUC within the baseline scenario and the ones chosen by stakeholders were very different, however concluded that Paddy field extent would decrease in the future to be replaced by more drought resilient agriculture; Perennials & Orchards and Field Crops. Outcomes from future scenarios propose that future LUC was driven by environment spatial factors such as elevation and climate, not soil suitability. With, first hand interviews suggesting it is indirect external factors such as, crop price that drive LUC. Overall the study provides steps towards dynamic LUC modelling where future scenarios have been tailored to details specified by the public through their participation.